Here we go again. (Economist, 2013)
The article focuses on Chinese President Xi Jinping and his interest in renewing ties with the U.S. Topics include the strained relations between the U.S. and China due to allegations of Chinese computer hacking into American computer systems, Xi's willingness to establish a 'great power relationship' with the U.S., and Xi's failure to implement political reform in China.